ANALISIS PERBEDAAN IMPLEMENTASI PROGRAM MERDEKA BELAJAR KAMPUS MERDEKA (MBKM) TERHADAP PENGEMBANGAN KETERAMPILAN ABAD 21 - Rais, Muh; Purnamawati; Syahrul (Almeera Education, 2025)
Abstract. Significant changes in the world of work and rapid technological advances require vocational graduates to master 21st-century skills such as critical thinking, communication, collaboration, and creativity. The Independent Learning and Independent Campus (MBKM) program is a transformative innovation implemented across all vocational higher education institutions in Indonesia. This study aims to comprehensively analyze the differences in MBKM implementation in developing 21st-century skills across three strategic vocational disciplines: technology, health, and economics. The study method used was a systematic literature review of 30 recent journals and academic documents to examine the dynamics, strategies, challenges, and unique achievements of each field. The results show fundamental differences in the implementation of MBKM in each vocational study program based on curriculum characteristics, industry partnerships, and institutional responses to the unique needs of the Industrial Revolution 4.0 era. Contextual recommendations are proposed to optimize the acceleration of 21st-century competencies in vocational education in Indonesia. Keywords: MBKM; Vocational Education; 21st Century Skills; Industrial Revolution 4.0